Anesthesia Risk and the Mucopolysaccharidoses: A Challenging and Changing Landscape - Walker, Robert W. M.; Garbarino, James (Journal of Child Science, 2018)
The mucopolysaccharidoses (MPS) are well known to present a high risk of anesthesia. Predominantly, this risk is not only related to upper airway issues but also to multilevel airway obstruction, respiratory morbidity, and cardiac issues. Before disease-specific treatment became available, the management of the untreated patients with MPS was regarded as the worst airway problem in pediatric anesthetic practice. The last 20 to 30 years have seen great advances in the treatment of the different types of MPS with hematopoietic stem cell transplantation (HSCT) being offered to children with MPS I Hurler sundrome since the 1980s, and more recently enzyme replacement therapy (ERT) becoming available for many MPS subtypes.These treatments have undoubtedly affected the relative risk involved with an anesthetic. HSCT improves markedly the upper airway and cardiac myocardial function and there is evidence that airway management is much more straightforward. ERT, on the other hand, improves obstructive sleep apnea and exercise tolerance, but the overall effect on the risk of anesthesia is less obvious and airway complications during anesthesia remain at a high level. The impact of improved anesthetic management in the same time frame is borne out by a reduced failed intubation rate in the literature.The management of the MPS patients necessitates a multidisciplinary approach presently widely practiced in pediatric centers, but successful modes of therapy increasing their life span have pushed many of the extreme anesthetic challenges into adult practice where most anesthetists will be unfamiliar with the problem. This is a problem that needs to be addressed, and solutions to this issue could be collaborative working between pediatric and adult practitioners or an international network of experts available for advice.
Keywords: anesthesia; mucopolysaccharidosis; airway management